KONTROL STRUKTUR TERHADAP PENYEBARAN BATUAN VOLKANIK KUARTER DAN GUNUNGAPI AKTIF DI JAWA BARAT - Sunardi, Edy (Bulletin of Scientific Contribution, 2014)
Distribution of Quaternary volcanic rocks and the position of the active volcanoes are relation with subduction activity. In the surface appearance of volcanic rocks and active volcanoes is controlled by fault structure. The purpose of this study was to determine the pattern of distribution of fault structure underlying the Quaternary volcanic rocks. The methods used by Landsat imagery analysis and delineate the age distribution of volcanic rocks. Since Late Tertiary to Quaternary fault structures have been formed either as a result of reactivation of old faults or as a new fault structures formed by tectonic younger. Based on the age of volcanic rocks and underlying fault pattern can be concluded that the tectonic activity and magmatism / volcanism never stops.